로즈힙의 영양학적 기능 및 생리활성에 대한 문헌적 고찰 - 정태환(Tae-Hwan Jung); 황효정(Hyo-Jeong Hwang); 신경옥(Kyung-Ok Shin) (한국식품과학회지, 2022)
This study was conducted to investigate the efficacy of rose hip utilization on various diseases. Rose hips are produced on a shrub native to Europe, and have been used for medicinal purposes and nutritional supplementation for centuries. It is rich in minerals, vitamins, and various functional compounds, including calcium, magnesium, phosphorus, potassium, selenium, vitamin B, vitamin C, and vitamin E, quercetin, catechin, β-carotene, β-sitosterol, polyphenol, flavonoid, taxifolin, ellagic acid, and salicylic acid. Extracts and powders of rose hips have been reported to contain antioxidant, free radical scavenging, and anti-inflammatory activity, and exert beneficial effects including amelioration of osteoarthritis, body fat reduction, anti-obesity activity, anti-bacterial activity, antidiabetic properties, and anti-cancer activity. Therefore, rose hips as a functional natural food may be considered effective for use in treating diseases including obesity, diabetes, osteoporosis, cardiovascular disease, and cancer. 본 총설은 로즈힙의 영양학적 기능성에 대한 선행 연구결과들을 조사하여 로즈힙의 다양한 효능들을 체계적으로 정리함으로써 로즈힙을 효과적으로 사용하기 위한 기초 자료를 제공하기 위해 작성되었다. 본문에서 언급한 것처럼 로즈힙에는 유용한 비타민 및 무기질 성분들이 풍부하고 β-카로틴, β-시토스테롤, 카테킨, 라이코펜, 폴리페놀, 플라보노이드, 프로안토시아닌, 퀘르세틴, 탁시폴린, 엘라그산 및 살리실산 등의 기능성 성분들이 다량 함유되어 있어 항산화 효과가 뛰어나며, 골관절염 개선, 체지방을 감소, 피부의 노화를 방지, 심혈관 질환률 감소, 항균·항당뇨 및 항암 효과가 뛰어나 기능성 식품으로서 활용 가능성이 매우 높다. 따라서 다양한 질환에 노출되고 있는 현대인들에게 화학적 합성물질이나 약물과 비교하여 천연 기능성 소재로써 비교적 안전하게 사용될 수 있는 로즈힙의 장점을 활용하기 위하여 로즈힙에 대한 연구가 지속될 필요가 있으며, 로즈힙은 천연 기능성 소재로서 다양한 질환을 예방 및 개선하는데 효과적으로 사용될 수 있다고 사료된다.